2001
DOI: 10.1021/es0012624
|View full text |Cite
|
Sign up to set email alerts
|

A Passive Sampler for the Determination of Airborne Ammonia Concentrations near Large-Scale Animal Facilities

Abstract: Few data are available on the ammonia emissions of large-scale outdoor animal facilities in arid climates such as those found in California's San Joaquin Valley. Passive samplers provide an ideal tool for studying such large and heterogeneous area sources, because they are inexpensive, portable, and fully self-contained. UC Davis passive ammonia samplers incorporate modifications on a previous design, the Willems Badge, for ease of analysis. Citric acid was chosen as a coating medium though it performed as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…In passive filter packs (no forced air), ammonia in the air is transported by diffusion to the filter where it forms a salt with the acid; in forced-air filter packs, convective flow transports ammonia. Rabaud et al 21 found no difference in performance among filters coated with citric acid, oxalic acid, tartaric acid, or H 2 SO 4 , but weak citric acid-ammonia bond reduced ammonia trapping in denuders 22 (discussed later). After the experiment, the filter is eluted, and the eluent is analyzed for NH 4 ϩ .…”
Section: Acid Scrubbers (Acid Traps Bubblers or Impingers)mentioning
confidence: 96%
See 1 more Smart Citation
“…In passive filter packs (no forced air), ammonia in the air is transported by diffusion to the filter where it forms a salt with the acid; in forced-air filter packs, convective flow transports ammonia. Rabaud et al 21 found no difference in performance among filters coated with citric acid, oxalic acid, tartaric acid, or H 2 SO 4 , but weak citric acid-ammonia bond reduced ammonia trapping in denuders 22 (discussed later). After the experiment, the filter is eluted, and the eluent is analyzed for NH 4 ϩ .…”
Section: Acid Scrubbers (Acid Traps Bubblers or Impingers)mentioning
confidence: 96%
“…Based on design, preparation, and analytical methods, filter packs have DLs of 0.2-2.8 g/filter 21,23,24 where the DL was 2-3 standard deviations (SDs) in the field blanks. The saturation limit of a filter pack is much lower than its stoichiometric capacity because of reduced mass transfer to the deeper, unsaturated layer through a "saturated" surface layer.…”
Section: Acid Scrubbers (Acid Traps Bubblers or Impingers)mentioning
confidence: 99%
“…Passive filter packs, adapted from Willems badges, 24 consisted of citric acid-coated Whatman filters supported 2 m above ground in 37-mm Gelman filter holders with 2-m pore size Teflon prefilters. 25 Passive filter samplers were collocated with all reference samplers. Linear regression of the rate of NH 3 -N accumulation in the passive filter (field blank corrected mass of NH 4 -N divided by time of exposure) to the air NH 3 -N concentrations measured by the reference method, for non-zero data, provided a slope and error of the slope for the best fit line through the data points and the origin.…”
Section: Nh 3 Emission Measurementsmentioning
confidence: 99%
“…In response to this challenge, we sought a more affordable method and designed a passive HNO 3 sampler from commercially available monitoring cassettes that are specified for vacuum sampling of particulate matter and gases for industrial hygienic sampling. Our sampler conceptually follows Bytnerowicz et al [2005] and is similar in appearance to Rabaud et al [2001] (Figure 1). Table 2 provides a complete listing of sampler components and prices as of June 2008.…”
Section: A Simple Passive Gaseous Nitric Acid Monitoring Techniquementioning
confidence: 99%